BER and outage probability for cooperative relay networks - Loh, Yi Hui (Nanyang Technological University, 2023)
The purpose of this report is to investigate the bit-error rate (BER) and the outage probability of the system. The cooperative relay system consists of three nodes or multiple nodes, where a source node conveys data to a destination node via a relay node. There are two different relaying protocols amplify-and-forward (AF) and decode-and-forward (DF). To evaluate the system’s performance, the BER and outage probability are commonly used as prime performance metrics. This report mainly focuses on simulating the computation of BER and outage probability rates using various M-ary modulation schemes such as BPSK over an AWGN channel, BFSK over an AWGN channel, QPSK over an AWGN channel, BPSK over Fading channel and QPSK over Fading channel. Additionally, this report analyzes the AF cooperative relay network protocol, which achieves a lower BER compared to an AWGN channel or fading channel.